Separation and purification of gases with molecular sieves. - Triebe, Robert W. (University of Ottawa (Canada), 1994)
Equilibrium adsorption constants were determined for CO, CO$\sb2$, NO, N$\sb2$, CH$\sb4$, C$\sb2$H$\sb4$, and C$\sb2$H$\sb6$ on various molecular sieves between 233 and 523 K. The molecular sieves tested for adsorption of these gases were 4A and 5A zeolite, 13X and a CaX zeolite, H-mordenite, a natural clinoptilolite and a carbon molecular sieve. The gas chromatographic method was used for all equilibrium measurements. Upon choosing the promising CO/N$\sb2$/clinoptilolite system for further studies, kinetic (diffusion) characteristics of each of these pure gases in the clinoptilolite ports was examined between 323 and 423 K using the gas chromatographic method. Pure gas and binary gas adsorption isotherms for the CO/N$\sb2$/clinoptilolite system were determined up to 1 atmosphere pressure at 303 K using the gas chromatographic method. Pure isotherms were fit with the Lanpmuir and Vacancy Solution Theory models. Pure gas modelling results were used to predict and compared to the experimentally determined binary gas isotherms. Separation of polar compounds from non-polar compounds was facilitated by inclusion of divalent cations in the zeolite micropores. Clinoptilolite showed great promise for various separations. The chromatographic method for measuring adsorption isotherms is limited in the measurement of rectangular isotherms, yielding errors dependant upon the accuracy of the gas blending system. The Wilson form of the VST accurately predicts the binary adsorption data.
Keywords: Engineering, Chemical.